Single citrate locksolution versus heparin lock solution for the prevention of complicationsassociated with long-term dwelling catheter in hemodialysis patients: a meta-analysis - YANG Lei; WANG Jia-sheng; QIU Jun; KANG Xiao-lan; LI Jia-yi (Linchuang shenzangbing zazhi)
Objective To compare effectiveness of single citrate lock solution versus heparin lock solution for prevention of complicationsassociated with long-term dwelling catheter in hemodialysis patients with Meta-analysis. Methods Comprehensive electronic search was performed using the following electronic databases: Cochrane library, PubMed, EMBASE, Ovid, VIP,Wan Fang, CNKI and CBM. The literature published before September of 2018 was searched. The randomized controlled trials(RCTs) on single citrate lock solution and heparin lock solution in hemodialysis patients were included. The included trials were evaluated for their quality with Cochrane systematic evaluation method, and software RevMan5.3 was used to conduct meta-analysis after extraction of the data. Results Ten randomized controlled trials were included with a total of 1 326 patients which were divided into the trial group(674 patients) and the control group(647 patients). The trail group had catheter dwelling days of 45 090, and the control group had the days of 43 031. High concentration citrate and heparin lock solutions were compared in three trials, middle and low concentrations of the two lock solutions in the resting seven trials. The meta-analysis showed, compared with those on heparin lock solution, the risk for bleeding in patients receiving citrate lock solution decreased,[RR=0.33, 95%CI(0.25～0.45), P<0.05],and the risk for catheter thrombosis in the citrate lock solution group was increased significantly[RR=1.90, 95%CI(1.60-2.25), P<0.05]. However, both of the groups were similar in terms of catheter-associatedbloodstreaminfection, puncture site infection, catheter dysfunction, thrombolysis treatment frequency, catheter-associated hospitalization and all-cause death, with no difference of statistical significance(P>0.05).Conclusions According to current evidence,citrate lock solution for hemodialysis patients with tunneled catheter can reduce risk for bleeding, but have higher risk for catheter thrombosis. Because of the limitation of samples and poor quality, more large samples and high quality randomized controlled prospective trials are required to provide better confirmation evidence, so as to support the above conclusion.